Analisis Kondisi Ekonomi Agregat Dan Daya Saing Sektoral Kota Jambi 2019-2023 - Dita Leila Alodia; Erni Achmad; Rosmeli (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to (1) identify and analyze the overall and sectoral economic conditions, and (2) identify and analyze the competitiveness of economic sectors in Jambi City during 2019–2023. The research employs secondary data with descriptive and quantitative analysis methods. The descriptive analysis using the growth formula shows that (1) the Gross Regional Domestic Product (GRDP) of Jambi City grew by 2.38%, reflecting post-pandemic recovery. Investment increased by 77.77%, and direct government expenditure increased by 14.86%, indicating stronger investment attractiveness and government efforts to support development and economic competitiveness. Based on the quantitative analysis using the Esteban-Marquillas Shift-Share method, (2) six leading sectors were identified: Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles, Accommodation and Food Service Activities, Information and Communication, Financial and Insurance Activities, Business Services, and Human Health and Social Work Activities, which were also found to be specialized and competitive sectors.